Integrity and Child Maltreatment at Child Care Centers : A Conceptual Paper - Rahim, Nur Rifhan A.; Razali, Nur Hanisah Mohamad; Jasmi, Zarith Sofia; Abd Halim, Siti Noorhaslina; Hassan, Nurfarhana; Rahim, Nur Syafiqah A. (Advances in Social Sciences Research Journal, 2024)
The Department of Social Welfare (JKM) reported 5572 child maltreatment cases until November 2022. According to the Deputy Women, Family and Community Development Minister, Datuk Siti Zailah Mohd Yusoff, the welfare department recorded a total of 336 child maltreatment cases in various categories involving day care centers, register and unregistered nurseries and kindergartens were reported in year 2021 to 2022. Child maltreatment or child abuse is defined as “all forms of physical, emotional ill-treatment, sexual abuse, neglect or negligent treatment or commercial or other exploitation, resulting in actual or potential harm to the child's health, survival, development, or dignity in the context of a relationship of responsibility, trust or power” (World Health Organization, 1999). With alarming statistics nationwide for several years consecutively, child abuse cases have sparks outrage to many; police, media, politicians, authorities, UNICEF representative and Tunku Mahkota of Johor. Taking the concept of IHSAN (care and compassion) under Malaysia MADANI, this study is timely and appropriate. Therefore, this conceptual paper analyzes the concept of integrity and child maltreatment at child care centers in Malaysia